PENGURANGAN RACUN AMONIA, BAHAN ORGANIK DAN PADATAN TERSUSPENSI DI MEDIA BUDIDAYA UDANG GALAH DENGAN BIOFILTER DARI BAHAN GENTENG PLASTIK BERGELOMBANG - Muslim Muslim (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractFish culture and shrimp culture has been developing rapidly during the last few decades, itis due to the increase of fish and shrimps demand. Increasing aquaculture activities especiallywith semi-intensive and intensive system have significant effect on waste production, whichhas to be removed or to be reduced quickly because will effect on fish in rearing tank andenvironment when through away to environment such as river and sea. The objective of thisstudy was to know the capability of corrugated plastic to remove or to reduce ammonia,organic matter and Suspended Solids (SS). The result of the study showed that theconcentration of ammonia, organic matter and SS in waste water reduced after were passedto corrugated plastic tank. Reducing of ammonia, organic matter and SS that occurred inshrimps rearing tank for culturing shrimp with treatment different protein concentrationcontain in meal fish were 32% and 28% with removal efficiency for ammonia were 10.95%and 14.37%; organic matter 49.02% and 19.94%; SS were 35.46% and 22.22%. Thistreatment can minimize increasing rate of ammonia, organic matter and SS, thus thistreatment can maintain water quality in rearing tank. So, it can be concluded that corrugatedplastic had capability to reduce or remove of ammonia, organic matter and SS.